Legal Protection For E-Bangking Customers (Perlindungan Hukum Terhadap Nasabah E-Banking) - Sofiyah, Siti; Apriani, Rani (Peneliti.net, 2024)
E-Banking is a facility provided by banks for their customers to make it easier for their customers to make money transactions online. At this time, people are familiar with the term e-banking, they usually use this facility to transact in buying and selling activities online. However, there are also many cases where e-banking belonging to customers has been breached. With this case, we must be more careful in maintaining the privacy of our e-banking data and of course the bank concerned must also be responsible for safeguarding customer property rights. Protection of customers is regulated in the 1945 Constitution (Article 1 paragraph 3), Law Number 7 of 1992 was changed to law number 10 of 1998 concerning Banking, Law Number 8 of 1999 concerning Consumer Protection, Law Number 11 of 2008 concerning Information and Electronic Transactions, Law Number 36 of 1999 concerning Telecommunications.